The Combined Use of Carbon Fiber on the Sides and Soffit of HighStrength RC Beams with Traditional Steel Bars and Steel Fiber Shear Reinforcement (Eurasian Journal of Engineering and Technology, 2023)
This study investigates the structural performance of high-strength reinforced concrete beams under shear forces using two combinations of shear reinforcement; the first combination option was provided as Stirrups (ST)-Carbon Fiber (CF), and the second option was provided by Steel Fiber (SF)-Carbon Fiber (CF). The steel fiber shear reinforcement was provided in two volume fractions, Vf=0.5%, and Vf=1.0%. Steel stirrups, on the other hand, come in two configurations, Φ8mm@300mm and Φ8mm@200mm, which are equivalent to the shear strength effects of 0.5% and 1.0% steel fiber content, respectively. A 45ᵒ inclined CF material has been externally applied on both sides of the tested beams in addition to the soffit part of the beams. A total of ten beams, including tow reference beams. The first reference beam was with no any form of shear reinforcement and the other beam was with CF at the soffit part of the beam only and without shear reinforcement. The results of four-point bending tests, including ultimate load capacity, failure mode, and deflection, were reported and analyzed. The results show that carbon fiber significantly enhances shear resistance regardless of whether the beam was reinforced with steel stirrups or steel fiber. However, the CF contribution is more pronounced by more than twice when highstrength beams are reinforced with steel fiber compared to steel stirrups. Furthermore, the result showed that the application of carbon fiber at the soffit part of the beam in comparison with the results obtained by Hayder A kadhim & Ali A. Sultan (2023) has a negligible effect on the shear strength, the mode of failure and load deflection behavior of the tested beams